1991
DOI: 10.1575/1912/3224
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of the sound generated by breaking waves

Abstract: in partial fulfillment of the requirements for the Degree of Doctor of Philosophy in Oceanographic EngineeringBreaking waves dissipate energy, transfer momentum from the wind to surface currents and breaking enhances the transfer of gas and mass across the air-sea interface. Breaking waves are believed to be the dominant source of sea surface sound at frequencies greater than 500 Hz and the presence of breaking waves on the ocean surface has been shown to enhance the scattering of microwave radiation. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(131 reference statements)
0
10
0
Order By: Relevance
“…By contrast the amplitude of the frequency peak near 100 Hz did not change substantially with tidal stage and is also substantially reduced in the cliff-top spectra. It is known that breaking (plunging) waves contribute to the ambient sound field at frequencies as low as 50 Hz (Vagel, 1989;Loewen, 1991). This may be an important contributor, given that the strong topographic break at the edge of the shore platform forces breaking at a similar location at all tidal stages.…”
Section: Frequency Of Ground Motionmentioning
confidence: 99%
“…By contrast the amplitude of the frequency peak near 100 Hz did not change substantially with tidal stage and is also substantially reduced in the cliff-top spectra. It is known that breaking (plunging) waves contribute to the ambient sound field at frequencies as low as 50 Hz (Vagel, 1989;Loewen, 1991). This may be an important contributor, given that the strong topographic break at the edge of the shore platform forces breaking at a similar location at all tidal stages.…”
Section: Frequency Of Ground Motionmentioning
confidence: 99%
“…By studying the evolution of the bubble cloud generated by the breaking wave, they formd that a significant proportion of the dissipated energy (up to SO%) is due to work done by the liquid in entraining air against buoyancy. Using data from similar experiments, Loewen (1991) [see also Loewen and Melville (1992)] showed that the energy dissipated by a breaking event is proportional to the initial volume of air entrained (Figure 1.8). This is consistent with the Loewen & Melville (1991b) dipole sound source model which suggested that for similar bubble size distributions, the total acoustic energy radiated is proportional to the volume of air entrained.…”
Section: Breaking Wave Sound and Dissipationmentioning
confidence: 98%
“…Ea was scaled by the square of the product of the center wavenumber of the surface wave packet kc and the depth of the wave tank h (Loewen & Melville, 1991a). (Loewen, 1991). Plant (1982).…”
Section: Spectral Dissipation Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Spilling and plunging breaking waves were created with a programmable wavemaker following the focused wave packet methods described by [18] and [19]. Wave trains of varying frequency were combined to produce a single breaking wave approximately 0.1 m high.…”
Section: Laboratory Observationsmentioning
confidence: 99%